Dream Activity in Narcoleptic Patients During the COVID-19 Lockdown in Italy - Scarpelli, Serena; Alfonsi, Valentina; D'Anselmo, Anita; Gorgoni, Maurizio; Musetti, Alessandro; Plazzi, Giuseppe; De Gennaro, Luigi; Franceschini, Christian (Frontiers in Psychology, 2021)
Some studies highlighted that patients with narcolepsy type-1 (NT1) experience high lucid dream frequency, and this phenomenon has been associated with a creative personality. Starting from the well-known “pandemic effect” on sleep and dreaming, we presented a picture of dream activity in pharmacologically treated NT1 patients during the Italian lockdown. Forty-three NT1 patients completed a web-survey during Spring 2021 and were compared with 86 matched-controls. Statistical comparisons revealed that: a) NT1 patients showed greater sleepiness than controls; b) controls showed higher sleep disturbances than NT1 patients, and this result disappeared when the medication effect in NT1 was controlled; c) NT1 patients reported higher lucid dream frequency than controls. Focusing on dreaming in NT1 patients, we found that a) nightmare frequency was correlated with female gender, longer sleep duration, higher intrasleep wakefulness; b) dream recall, nightmare and lucid dream frequency were positively correlated with sleepiness. Comparisons between low and high NT1 lucid dreamers showed that patients more frequently experiencing lucid dreams reported a greater influence of dreaming during wakefulness, especially concerning problem-solving and creativity. Overall, our results are consistent with previous studies on pandemic dreaming carried out on healthy subjects. Moreover, we confirmed a link between lucidity and creativity in NT1 patients. Considering the small sample size and the cross-sectional design, our findings cannot provide a causal relationship between lucid dreams and the COVID-19 lockdown. Nevertheless, they represent a first contribution to address future studies on this issue, suggesting that some stable characteristics could interact with changes provoked by the pandemic.